Build Students' Research Skills Through Collaborative Real-World Analysis-Based Learning - Sinensis, Arini Rosa; Firdaus, Thoha; Saulon, Butch O (Indonesian Review of Physics, 2022)
Research skills are one of the skills that need to be built for students to face the challenges of the 21st Century. Therefore, this study aims to build research skills through the Collaborative Real-World Analysis (CReW-A) learning model. This study uses the One-Shot Case Study design. Respondents came from 21 Physics Education students who were grouped into seven research groups. Research skills were observed using a 5-point Likert rating scale observation sheet. Students research skills were analyzed using Rasch modeling, the Wright map technique combined with the Logit Value of Person (LVP). After applying the Collaborative Real World Analysis (CReW-A) learning model for four weeks, students' research skills were well-developed in most research groups. So, the Collaborative Real World Analysis (CReW-A) learning model that has been implemented has been able to build the research skills of physical education students. Therefore, in the future, students can use these skills to innovate to face the challenges of the 21st Century.